Empirical generalisations in customer mindset metrics. Issue 1 (30th May 2021) - Mecredy, Philip J.; Wright, Malcolm J.; Feetham, Pamela M.; Stern, Philip
Abstract: Two very well‐known empirical generalisations in marketing are Double jeopardy (DJ) and the duplication of purchase law (DoP). These generalisations provide important insights into consumer buying behaviour but require ongoing replication and extension to determine the conditions under which they hold. Surprisingly, despite growing recognition of the role of customer mindset metrics in brand choice, DJ, and DoP have not been extensively tested within this context. We therefore analyse survey data ( n = 1862) in three repertoire and two subscription markets to determine whether two key mindset metrics, brand awareness and brand consideration, also follow DJ and DoP patterns. Our study successfully demonstrates that brands with low recognition suffer twice with lower unaided brand recall and lower purchase consideration. While brand recall and consideration follow a linear DJ trend, brand recognition and consideration follow an exponential DJ trend. We also confirm the existence of Duplication of Awareness and Duplication of Consideration patterns. Brands share greater awareness or consideration levels with other highly recognised or considered brands than with lowly recognised or considered brands. However, contrary to the DoP law, we find consistent market partitioning, with category buyers who are aware of, or consider smaller brands also being aware of, or considering other smaller brands at a slightly greater rate than expected. We provide possible explanations for differing DJ slopes and duplication partitions, as well as theoretical and managerial implications.